A comparative study of automatic text summarization system performance - Vlainić, Marta (Array, 2013)
This paper provides a comparative study of commercial and academic automatic document summarization tools: Microsoft Word, SweSum, SHVOONG and Online Brevity Document Summarizer. Also, these automatic systems are compared to human summarization techniques and analyzed, aiming to reveal which automatic summary achieves the best results in comparison with the human summarization techniques. Results of the experiment show that the most high-quality automatic summary was generated by Online Brevity Document Summarizer.